A Survey on Unauthorized UAV Threats to Smart Farming - Peng Chen; Shihao Yan; Helge Janicke; Arash Mahboubi; Hang Thanh Bui; Hamed Aboutorab; Michael Bewong; Rafiqul Islam (Drones)
The integration of Internet of Things (IoT) and unmanned aerial vehicles (UAVs) in smart farming has revolutionized agricultural practices by enhancing monitoring, automation, and decision-making to improve agricultural productivity and sustainability. However, the widespread use of these technologies has also introduced new security challenges, particularly the risk of interference from unauthorized UAVs. This survey provides an analysis of the threats posed by unauthorized UAVs to smart farms, highlighting potential vulnerabilities such as data interception, communication jamming, and physical damage. This paper first explores recent advancements in IoT and UAV technologies, which are integral to the functioning of smart farms. Then, we present an analysis of unauthorized UAV threats to smart farms and evaluate the current state-of-the-art UAV countermeasure technologies. By examining these emerging threats and potential solutions, this survey aims to inform researchers, engineers, policymakers, and practitioners involved in smart farming about the critical need for enhanced anti-UAV systems. Additionally, it highlights the necessity for airspace management authorities to recognize the risks posed by unauthorized UAVs, invest resources in protective measures, and address the challenges associated with securing smart farms against unauthorized UAV threats.